A lifespan perspective on multi-professional musicians: does music education prepare classical musicians for their careers? - López-Íñiguez, G.; Bennett, Dawn (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2019)
Many professional musicians would describe their careers as somewhat different to the careers they imagined when they were students. This study sought to understand the relationships between musicians’ higher music education experiences and their professional work, and to expose the adaptive strategies they employ to sustain their work. The researchers amassed in-depth career narratives from eight musicians who were highly respected international performers. The musicians were also ‘multi-professional’ musicians in that they were recognised as highly proficient in multiple different roles. Narratives were analysed using selection, optimisation and compensation (SOC) theory. The results suggest that essential professional capabilities should be emphasised in the core curriculum of higher music education. A novel finding is that musicians who identify themselves as learners may be better able to create and sustain a career in music.